Study on characteristics of ammonia alkali white mud and mechanical properties of preparation of fluid solidified soil - Fu, Shifeng; Li, Zhiquan; Zhang, Guangtian; Zhang, Biao; Zhang, Yanjia (Frontiers in Materials, 2024)
To address the challenges posed by the significant quantity of ammonia-alkali white mud, this study explores the preparation of fluid solidified soil using ammonia-alkali white mud, mineral powder, and fly ash. The findings reveal that ammonia-alkali white mud primarily comprises sulfate, carbonate, and soluble chloride salt, with an alkaline solution and a well-developed pore structure. Optimal fluid solidified soil formulation, comprising 30% white mud, 30% salt mud, 25% mineral powder, 10% fly ash, and 5% calcium oxide, yields a slurry fluidity of 176 mm and a compressive strength of 3.98 MPa at 28 days.Microscopic analysis highlights AFt and C-S-H gel as the principal hydration products of fluid solidified soil. The fine particles of calcium carbonate in ammonia-alkali white mud fill the structural pores and intertwine with the hydration products, facilitating the formation of a dense structure, which constitutes the primary source of strength in fluid solidified soil. Furthermore, the heavy metal content of the solidified soil aligns with the first type of land use requirements outlined in the GB 36600-2018 standard, and the toxicity of the leaching solution adheres to the emission concentration limit stipulated by GB 8978-1996.